Interpretation and Visual Poetics in Medieval and Early Modern Texts
1 online resource.
Keywords: Focusing on literary and non-literary works alike, Interpretation and Visual Poetics in Medieval and Early Modern Texts places visual and material aspects of literary study at the center of the interpretive process. The essays in this collection explore new and traditional areas of research from hermeneutics, to codicology and history of the book, to cultures of sound and the digital humanities. They address the texts themselves, as well as their early manuscripts and subsequent printed and digital editions. The contributors collectively cover a time span of over 1000 years, and begin with the Mediterranean, focusing on texts produced in Italy and the Languedoc regions, then radiate outward to analyse the texts' material containers (manuscripts, print, and digital editions) that are now housed worldwide. Contributors are: Michelangelo Zaccarello, Daniel O'Sullivan, Valerio Cappozzo, Jelena Todorović, Christopher Kleinhenz, Mirko Tavoni, Isabella Magni, Francesco Marco Aresu, Dario Del Puppo, Beatrice Arduini, Giovanni Spani, Furio Brugnolo, Teodolinda Barolini, Alessandro Vettori, Marcello Ciccuto, Marco Veglia, Michael Papio, and Anthony Nussmeier.